Lipid-lowering medication for secondary prevention of coronary heart disease in a German outpatient population: the gap between treatment guidelines and real life treatment patterns - Ruof, Jörg; Klein, G.; März, Winfried; Wollschläger, H.; Neiss, A.; Wehling, Martin (Preventive medicine, 2002)
Background. Few published data in particular from the United States indicate that the implementation of guidelines for prevention of coronary heart disease (CHD) is far from optimal. The objective of our study was to identify the type and prevalence of lipid-lowering medications in a German outpatient CHD population and to examine the impact of applied treatment regimens on serum lipid levels. Methods. Retrospective analysis of the washout phase of 2,856 CHD patients requiring lipid-lowering medication. Data are derived from a multicenter, randomized, open-label, parallel group clinical trial comparing the safety and efficacy of atorvastatin versus simvastatin in 591 centers in Germany. Medical history, physical examination, and serum lipid levels were obtained at the beginning of the washout phase (Week −6) and at the end of the washout phase (Week −1, i.e., 5 weeks after the discontinuation of all prior lipid-lowering medications). The data at Week −6 represented the lipid levels under real life conditions. The difference from the data at Week −1 reflected the therapeutic effects achieved by the previous lipid-lowering treatment. Results. The mean low-density lipoprotein cholesterol (LDL-C) level at Week −6 was 173.4 ± 42.5 mg/dl. Only 176 (6.2%) of 2,856 CHD patients were found to meet the target LDL-C level of <115 mg/dl at Week −6, only 76 (2.7%) patients had LDL-C levels <100 mg/dl, and 363 (12.7%) patients had LDL-C levels <130 mg/dl. After discontinuation of all prior lipid-lowering medications, mean LDL-C increased to 187.2 ± 44.0 mg. This means that only a marginal 7.4% reduction in LDL-C level was achieved under real life treatment conditions. This limited LDL-C reduction was due mainly to the low prevalence of lipid-lowering treatment (65.5% of patients did not receive any medication at all) and inadequate dosing. With respect to the effect on LDL-C and total cholesterol, statins alone were superior to fibrates. Conclusion. The study shows that there is a wide gap between treatment guidelines and real life treatment patterns in Germany. Awareness of the risks of high cholesterol levels has to be increased among both patients and physicians. Available treatment guidelines should be better implemented.